Utilization of garlic and meniran flour by repelleting method in feed for preventive and curative efficacy of Aeromonas hydrophila in catfish Clarias sp. - Wahjuningrum, Dinamella; Kurniawan, Dadang; Setyotomo, Karno; Setiawati, Mia (Jurnal Akuakultur Indonesia, 2012)
This research was purposed to determine the effective dose of meniran and garlic flour in feed by repelleting method for preventive and curative efficacy to the infection of Aeromonas hydrophila in catfish. The treatment tested were eight different dosages of garlic and meniran meals (2:1). Those four dosage used to preventive treatment namely A (0.1%), B (1.1%), C (2.1%), and D (3.1%), the other four used to curative treatment namely E (0.2%), F (2.2%), G (4.2%), and H (6.2%). The preventive treatments were given for two weeks before challenging test. The curative treatment was performed on 2nd–8th day after challenging test. Challenging test was carried out by intramuscularly injecting of 0.1 mL A. hydrophila (108cfu/mL) into the fish. Parameters observed were feeding response, growth rate, survival rate, clinical symptoms, wound healing, and organs morphology. The result showed that the survival rate of preventive treatment was 40±40% for A and B, 60±20% for C, and 20±20% for D. The survival rate of curative treatment was 33.33±11.55% for E, 46.67±11.55% for F, 33.33±11.55% for G, and 26.67±11.55% for H. The results indicated that the preventive treatment was more effective than the curative treatment, presumably because the immunostimulatory activities on preventive was better than curative. Keywords: garlic, meniran, repelleting, Aeromonas hydrophila, catfish